Candida and Enterobacter co-infection in a case of periampullary carcinoma with obstructive jaundice - Toleti, Sunita; Manivasagan, Manisegaran; Prudhve, Sumana; Raavi, Tapasya; Shaik, Naseema; Myneni, Ramesh B (International Journal of Research in Medical Sciences, 2017)
Pancreatic infection remains a significant clinical problem, with substantial morbidity and mortality. We report a case of periampullary carcinoma and culture of the pancreatic pus and bile showed growth of Candida albicans and Enterobacter species. Amphotericin B therapy is effective in clearing Candida infection, but affected patients have a high associated mortality.